In the shadow of the dark twin – proving criminality in money laundering cases. Issue 4 (3rd October 2016) - Murray, Kenneth
Abstract : Purpose: This paper aims to highlight the persistent influence of the concept of "predicate offence" in respect of how the crime of money laundering is conceived and discussed, and to discuss how this inhibits the ability to prosecute the crime even where, as is the case in the UK, "predicate offence" is not a requirement of the relevant legislation. Design/methodology/approach: Discussion of a recent UK Supreme Court judgment, R v GH, in particular, how the import of it appears to contrast with perceptions offered by the experience of two recent money laundering convictions on Scotland, where no evidence was led on establishing the money was criminal before the criminal act was libelled as money laundering. Design of modern money laundering schemes are illustrated and assessed in terms of how they can be prosecuted in the context of prevailing interpretations of the law. Findings: The effectiveness of the UK money laundering offences as set out in the Proceeds of Crime Act of 2002 requires revaluation. Clarification is required in respect of how criminality in such cases can be proved. Consideration should be given to introducing new legislation targeted at the transmission of money or value under the cover of false documentation. Research limitations/implications: Clarification is required on how the concept of "irresistible inference" as established by R v Anwoir can be applied to money laundering cases in light of the R v GH judgement of the UK Supreme Court. Practical implications: Upgrade of law enforcement knowledge base and investigation skills is required to prosecute existing money laundering offences more effectively, but the lack of clarity as to what will suffice as proof of criminality serves to inhibit the investigation of these crimes as well as their prosecution. Social implications: Protection of democracies, democratic institutions and the communities they serve from the corrupting influence of laundered criminal money through more effective prosecution of money laundering offences. Originality/value: To encourage discussion on whether the relevant legislation remains fit for purpose and what practical measures can be taken to improve it.